N-(2,3,4-Trifluorophenyl)phthalimide - Fu, Xian-Shu (International Union of Crystallography, 2010)
In the title compound, C(14)H(6)F(3)NO(2), the benzene ring and the phthalimide ring system make a dihedral angle of 60.12 (7)°. Weak intermolecular C—H⋯O and C—H⋯F hydrogen bonds are present in the crystal structure.